KEHIDUPAN PEREMPUAN KULI ANGKUT KELAPA SAWIT DI DESA SUKA MAKMUR KECAMATAN GUNUNG SAHILAN KABUPATEN KAMPAR - MARVIANA, ELYK; ", INDRAWATI (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Rural society in Indonesia apply economic strategy where some of family members work for money. The family members work in some sectors; agriculture, self belonging business, or labour. In this kind of strategy, women and men have same role and responsibility to work in agriculture or other field. Among poor families, women's tole is stronger than middle up families. It can be seen from women working as a porter in palm plantation in Desa Suka Makmur.The problem in this reseach are: 1. What is the characteristic of a woman porter in palm plantation in Desa Suka Makmur? 2. How does a woman porter run her role in the family? 3. What is the effect of a working woman in family?. The purpose of this tesearch is to find out the chatacteristics of women porter in palm plantation in Desa Suka Makmur, how they run their families, and the effect of workin women in the family. Subject in this research is housewives working as palm porter. They are 6 women. Information is also gotten from some informants, which are their husbands. Writer ised qualitative approach, with purposive sampling technique. Data collection technique is done by interview, observation and documentation. For women porter in Desa Suka Makmur, Being a palm porter in palm plantation is a choice to help their husband. Being an extra bread winner without forgetting their responsibilities as wives and mother.Key word: women, porter, double boarden